Edukasi Penyuluhan Pencegahan Karies gigi Sebagai Upaya Mengurangi Risiko Karies pada Anak SDN 02 Sukasari Desa Sukasari Kabupaten Kepahiang - Dennisa Novita Agustin; Monica Sella; Tati Herpianti; Yelvi Cornelia; Zakiah Septi Ardita; Fiya Diniarti; Meri Epriana Susanti (Utami Publisher, 2026)
Dental caries is one of the most common health problems among elementary school children and is generally caused by improper toothbrushing habits, frequent consumption of sugary foods, and low levels of knowledge regarding oral and dental health. This caries prevention education activity was carried out for students at SDN 02 Sukasari with the aim of increasing children’s knowledge and awareness about caries prevention through interactive counseling, demonstrations of proper toothbrushing techniques, and education about foods that affect dental health. The implementation methods included delivering educational material, hands-on practice, and simple assistance provided by community service (KKN) students. The results of the activity showed an increase in students’ understanding and behavior regarding the importance of maintaining oral and dental hygiene. This intervention proved effective as a promotive and preventive effort to reduce the risk of dental caries in children and is recommended for continuous implementation in other school environments.